Seasonal and intra-populational diet variation in the Colombian Swamp frog Pseudopaludicola pusilla (Anura Leptodactylidae). Issue 6 (2nd November 2021) - Atencia-Gándara, Pedro L.; Torres, Richard A.; Diaz-Perez, Jorge A.
Abstract : Diet is a fundamental aspect of the ecological niche of amphibians and usually varies intra-specifically in response to extrinsic environmental and intrinsic individual factors. Phenotypic variations among individuals can generate intrapopulation differences in trophic resource use, which could have important ecological and evolutionary implications in amphibian populations. Here, we studied the intrapopulation dietary variation of the frog Pseudopaludicola pusilla in an anthropic savanna of the Colombian Caribbean region, considering the effects of seasonality and sex on the size, amount, prey composition and dietary individual specialization. We collected 44 adult frogs during the dry season and 46 during the rainy season and analyzed their stomach contents to determine their dietary composition. Our results indicate that P. pusilla is a generalist and opportunist predator, feeding mainly on insects of the orders Orthoptera, Coleoptera and Hymenoptera, which were the most important prey categories due to their numeric, volumetric and frequency contributions. We observed seasonal variations regarding volumetric prey composition and the importance value of each prey category in the populational diet. Individuals of P. pusilla consume more prey items during the rainy season and bigger prey during the dry season, but the volume of stomach contents did not vary seasonally. Males and females of P. pusilla consumed a similar number of prey items, but females ingested more voluminous prey and had greater volumes of stomach contents than males. Additionally, we observed a pattern of dietary individual specialization, which was not related to morphological trade-offs and did not differ among seasons. These findings contribute to the understanding of the seasonal dynamics of the use of trophic resources by anurans and the effect of sex on dietary characteristics of P. pusilla, in environments strongly influenced by climatic seasonality.